Law Enforcement and Investigation of Cybercrime in Albania - Dushi, Desara; Bërdufi, Nertil (European Scientific Journal, ESJ, 2017)
Since 2000 until 2016, the Internet has expanded at an average rate of 918,3% globally; currently, around 4 billion people are online. Cyberspace today is one of the greatest legal challenges which have stimulated another form of crime, creating an environment for new methods of crime. Now, almost all crimes can be committed with the use of computers. This paper analyzes the procedures of cybercrime investigation according to the Albanian legislation such as handling of electronic evidence and the methods and tools of investigation. The paper deals also with the issues of cooperation with Internet Service Providers (ISP) and regional and international cooperation in the fight against cybercrime. Finally, the paper analyzes the work and progress of the new Cybercrime Investigation Units. This includes some interviews with cybercrime investigation agents providing information on the process of investigation of these crimes in Albania and the challenges faced by them.